2021
DOI: 10.3389/fmed.2021.772578
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Biometry of Primary Angle-Closure Disease in Younger Patients

Abstract: Background: The purpose of this study was to analyze the ocular biometric parameters of primary angle-closure disease (PACD) in younger patients and compare them with those of elderly patients.Methods: This clinic-based, cross-sectional study included 154 eyes of 154 patients with PACD, consisting of 77 eyes of patients aged 40 years or younger and 77 eyes of patients older than 40. The PACD case definition was compatible with the ISGEO definition. Anterior segment parameters were measured by ultrasound biomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Thus thinner ciliary body in eyes with PAC/PACG might be a manifestation of ciliary muscle atrophy related to aging, as showed in histological [20] and biometric [21][22] studies. However, thinner ciliary body thickness has been found in younger patients with PAC disease [15] , which indicates age might not be major factor. Therefore, we applied PSM to diminish the effect of age in this study, and thinner ciliary body was still observed in eyes with PAC/PACG.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thus thinner ciliary body in eyes with PAC/PACG might be a manifestation of ciliary muscle atrophy related to aging, as showed in histological [20] and biometric [21][22] studies. However, thinner ciliary body thickness has been found in younger patients with PAC disease [15] , which indicates age might not be major factor. Therefore, we applied PSM to diminish the effect of age in this study, and thinner ciliary body was still observed in eyes with PAC/PACG.…”
Section: Discussionmentioning
confidence: 95%
“…Another study indicated the younger patients with PAC disease presented thinner and more anteriorly rotated ciliary body than the older ones [15] . These studies indicated that thinner ciliary body thickness might also be a predisposing factor for special kinds of angle closure glaucoma such as APAC and malignant glaucoma.…”
Section: Discussionmentioning
confidence: 96%
“…HSK is a common, potentially blinding corneal diseases characterized by recurrent infection (9). Recurrent HSK can lead to stromal inflammation or neurotrophic keratitis, resulting in corneal perforation or full-thickness corneal scarring that requires PK (15). Combined or sequential PK and cataract surgery are well-established surgical treatments for corneal diseases coexisting with cataract due to their own advantages.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of age-related variations in AM onset is not clearly understood. Young PACG patients always demonstrate characteristics of more anteriorly located lenses, thinner and anteriorly rotated ciliary bodies, thicker choroids, and shorter axial length compared with older patients [ 38 ]. These anatomic features are now consistently perceived as risk factors for AM [ 37 ].…”
Section: Discussionmentioning
confidence: 99%